Mucoadhesive Film Forming Spray for Buccal Drug Delivery: A Review - Reem Wael Shahadha; Nidhal Khazaal Maraie (College of Pharmacy / Mustansiriyah University, 2023)
Film-forming sprays provide a number of advantages over conventional topical treatments, including equal medication distribution and dosing, increased bioavailability (increase local drug concentration), and less irritability (Dosing frequency). Polymers and excipients that improve the characteristics of preparations and increase the stability of active substances are the building blocks of mucoadhesive film-forming sprays. Films made from diverse combinations of polymer and excipient exhibited a wide range of characteristics. This reveiw examines the many types of polymers and excipients, the different types of sprayers, the different evaluations, as well as the essential criteria that are involved in defining the sprayability and film properties. This comes to the conclusion that natural and synthetic polymers with viscoelastic properties can both be employed to optimize the administration of buccal drugs.